Facilitating Factors and Barriers to Weight Management in Women: Physician Perspectives - Renee E. Walker; Jennifer Kusch; Jennifer T. Fink; David A. Nelson; George Morris III; Jessica Skalla; Ron A. Cisler (Journal of Patient-Centered Research and Reviews, 2018)
Purpose: The complexity of addressing overweight and obesity in women has been an ongoing public health and health care challenge. While the mechanism for addressing overweight and obesity in women remains unclear, it has been speculated that disparities in overweight and obesity by race and gender contribute to the complexity. The purpose of the present study was to examine perceptions of primary care physicians when discussing weight management with their patients.